ANALISIS KEAKURATAN HASIL PENERJEMAHAN GOOGLE TRANSLATE DENGAN MENGGUNAKAN METODE BACK TRANSLATION - Jumatulaini, Jumatulaini (Departemen Pendidikan Bahasa Arab, 2020)
This research analyses comparison between the original Arabic text and the translation back to Arabic by Google Translate on Arabic newspapers. To achieve test the accuracy of text according to translated theory. Then researchers use qualitative descriptive method of research with translation method back translations that is, a validation tool that is widely used in international research settings and original documents compared to translation results Back to see the inconsistencies, and if nothing of the translation is considered equivalent. Based on the results of the study the accuracy results of Google Translate is inaccurate, but understanding of the meaning text still understandable. As for inaccuracies of translations found such as linguistic studies such as syntactic, semantics, mistakes in writing numbers, lack of words, reduction.